Penguatan Receptive Skills Santri Melalui Pendekatan Mastery Learning dalam Pembelajaran Al-Qur’an di Pondok Pesantren - Baharun, Hasan; Dini, Alqoyla Rosabila (Program Pascasarjana Universitas Ibrahimy, 2019)
This study presents the strengthening of santri receptive skills through the mastery learning approach of al-Quran learning in pesantren. Receptive skills as competencies that must be possessed by santri related to listening and reading skills of the Qur'an must be possessed by every person santri. Therefore a mastery learning approach is needed in realizing the skills of these students. This study uses qualitative with a case study. This research site is Pondok Pesantren Nurul Jadid, Paiton, Probolinggo, East Java. The results showed that the mastery learning approach in strengthening students' receptive skills of the Qur'anic learning in Nurul Jadid was carried out through several stages of learning carried out through four stages; that are; (1) orientation, (2) perception, (3) presentation, and (4) evaluation. Based on this study, an answer was found that the mastery learning approach was able to strengthen the santri's receptive skills to reading the Qur'an goodly and correct, understanding of the rules of tajwid, and more importantly, the santri is able to continue at the next level.